Antibacterial activity of guava, moringa, camphor bush and pelargonium extracts against bacterial wilt (Ralstonia pseudosolanacearum sp. nov.) of potato - Onduru Okeyo, G.; Charimbu, M.K.; Nyaanga, J.; Mendes, T. (Elsevier, 2022)
Bacterial wilt (Ralstonia pseudosolanacearum sp. nov.) is a major disease devastating global potato production. Proposed management options are mostly expensive and ineffective. This has necessitated efforts to develop cheaper and eco-friendly management options such as use of botanicals. Antibacterial activity of ethanol and acetone plant extracts from guava (Psidium guajava), drumstick (Moringa oleifera), camphor bush (Tarchonanthus camphoratus) and pelargonium (Pelargonium zonale) against R. pseudosolanacearum sp. nov. was evaluated in-vitro at a concentration of 100 mg/mL of 1 % Dimethlysulfoxide (DMSO) using disk diffusion technique. The R. pseudosolanacearum sp. nov was isolated from infected haulms collected from potato growing field at the University of Nairobi. The most effective extracts were subjected to further screening at different concentrations to determine their minimum inhibitory concentrations (MICs). All the four plant extracts showed varied antibacterial efficacy. P. zonale leaves extract was the most effective with growth inhibition zone of 18.73 mm and 18.60 mm for ethanol and acetone solvents respectively. The average of growth inhibition zones for each plant extract was not significantly different at p <= 0.05 among extraction solvents. The minimum inhibitory concentration (MIC) results showed that antibacterial activity of P. zonale and P. guajava leaf started at 6.25 mg/mL with growth inhibition zones of 7.67 and 8.0 mm for ethanol and acetone solvents respectively. P. zonale and P. guajava leaf extracts exhibited significantly higher antibacterial activity at p <= 0.05 compared to other extracts. Thus, further research should be conducted to assess their antibacterial potency against R. pseudosolanacearum sp. nov. both in-vivo and under field condition.(c) 2022 The Author(s).